4(u-5)(-u+2)=0

Simple and best practice solution for 4(u-5)(-u+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(u-5)(-u+2)=0 equation:


Simplifying
4(u + -5)(-1u + 2) = 0

Reorder the terms:
4(-5 + u)(-1u + 2) = 0

Reorder the terms:
4(-5 + u)(2 + -1u) = 0

Multiply (-5 + u) * (2 + -1u)
4(-5(2 + -1u) + u(2 + -1u)) = 0
4((2 * -5 + -1u * -5) + u(2 + -1u)) = 0
4((-10 + 5u) + u(2 + -1u)) = 0
4(-10 + 5u + (2 * u + -1u * u)) = 0
4(-10 + 5u + (2u + -1u2)) = 0

Combine like terms: 5u + 2u = 7u
4(-10 + 7u + -1u2) = 0
(-10 * 4 + 7u * 4 + -1u2 * 4) = 0
(-40 + 28u + -4u2) = 0

Solving
-40 + 28u + -4u2 = 0

Solving for variable 'u'.

Factor out the Greatest Common Factor (GCF), '4'.
4(-10 + 7u + -1u2) = 0

Factor a trinomial.
4((-5 + u)(2 + -1u)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-5 + u)' equal to zero and attempt to solve: Simplifying -5 + u = 0 Solving -5 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + u = 0 + 5 Combine like terms: -5 + 5 = 0 0 + u = 0 + 5 u = 0 + 5 Combine like terms: 0 + 5 = 5 u = 5 Simplifying u = 5

Subproblem 2

Set the factor '(2 + -1u)' equal to zero and attempt to solve: Simplifying 2 + -1u = 0 Solving 2 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1u = 0 + -2 -1u = 0 + -2 Combine like terms: 0 + -2 = -2 -1u = -2 Divide each side by '-1'. u = 2 Simplifying u = 2

Solution

u = {5, 2}

See similar equations:

| (w+7)(w+2)=0 | | 50+20x=18 | | 25w^6+35w^3=0 | | (x+20.6)*0.604+(65-6.5-0.1*x-2.06)*0.471=150 | | -7(x-2)-3(4-x)=22 | | 2x+186=10x-6 | | 6x^3+3x^2+8x+4= | | 72+x+(x+2)=360 | | 31-4x=5x+15 | | 33-(2c+3)=2(c+5)+c | | x^2+13+6x-4=-3x-9 | | 6-3i/5-6i | | 4k-8/24-12k | | 3+x+(6x+7)= | | x*175=21 | | x*120=18 | | 9x+6=8x-12 | | x^2-3x+8=3x-6 | | -3x+-15=9 | | 6x+7.33=7 | | 140+x+(x-6)=360 | | 28+n=0 | | 2logx-log(2x-10)-1=0 | | 4.5q-2.6-5.7q=-2.2q-3.6 | | y=5x+43 | | 8/9x-2/3=6 | | 2x-39=25 | | 8(10x+10)=80x-2 | | 6x+272=y | | 80x^6y/2x^7 | | 0.18x+21.49=y | | -7*h=476 |

Equations solver categories